Образование как открытая общественно-государственная система - Сатенова, С.Г. (My University, 2013)
Development of regional system of the general secondary education is considered on the basis of system understanding of the pedagogical phenomena, in a context of an educational situation, taking into account the leading methodological priorities influencing a condition of a domestic education system as a whole.